Synthesis of symmetrically and unsymmetrically substituted cationic diborane(4) compounds with distinct structural motifs and properties - Filbeck, Erik; Kistner, Lucas; Vogler, Daniel; Bučak Gasser, David; Flórido Martins, Lilliana; Schöner, Maximilian; Kaifer, Elisabeth; Himmel, Hans-Jörg (European journal of organic chemistry, 2022)
The introduction of electron-donating, bridging guanidinate substituents in diborane(4) compounds allows the synthesis of a variety of new cationic diborane(4) compounds. In this work, strategies for the directed synthesis of cationic di- and tetraboron compounds are presented, leading to the synthesis and complete characterization of several new compounds with distinct structural motifs, all exhibiting BII atoms directly bound to each other. Hence, we report on tetracationic donor-acceptor cyclophanes with diboron donor linkers and organic π-acceptor units, on paddlewheel-type cationic diboranes, and on unsymmetrically-substituted monocationic diboranes.